Periods of weed interference in garlic crop (Acta Scientiarum. Agronomy, 2024)
Garlic cultivation holds significant importance in Brazil. However, research on garlic crops is currently limited and outdated, highlighting the necessity for new studies, particularly focused on enhancing weed management and optimizing the use of agricultural inputs. This study aimed to assess the extent of yield losses attributed to weed interference and the specific periods during which weed interference impacts garlic crop yields in the state of Santa Catarina, Brazil. The experiments were conducted in Curitibanos, Santa Catarina State, Brazil, during 2019 and 2020, using the garlic cultivars Chonan and Ito, respectively. A randomized block experimental design was employed, consisting of 16 treatment groups with four replications. The design incorporated a 2Ã—8 factorial arrangement, involving two weed management strategies (coexistence and control) and eight crop-weed coexistence periods (0, 15, 30, 45, 60, 90, 120, and 130 days after crop emergence – DAE). The study evaluated the weed community and recorded data on the number of bulbs, bulb diameter, as well as total and commercial bulb yields of garlic crops. The results indicated average losses of 24.3% in total bulb yield and 28.9% in commercial bulb yield. Critical periods for effective weed control were identified as 6 to 126 DAE in 2019, 5 to 126 DAE in 2020 for total yield, 3 to 126 DAE in 2019, and 5 to 126 DAE in 2020 for commercial bulb yield. Consequently, it is imperative to maintain garlic crops weed-free throughout most of their growth cycle.